Prevalence and Association of Congenital Anomalies According to the Maternal Body Mass Index: Cross-Sectional Study - Moraes, Carolina Leão de; Mendonça, Carolina Rodrigues; Melo, Natália Cruz e; Amaral, Waldemar Naves do (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To evaluate and compare the prevalence of structural congenital anomalies (CAs) according to maternal body mass index (BMI).Methods The present cross-sectional study involved pregnant women with fetuses diagnosed with structural CAs through morphological ultrasonography between November 2014 and January 2016. The nutritional status of the pregnant women was classified according to the gross value of the body mass index. The pregnant women were categorized into four groups: low weight, adequate weight, overweight, and obesity. Statistical analysis was performed using Stata/SE version 12.0 (Stata Corporation, College Station, TX), with values of p ≤ 0.05 considered statistically significant.Results A total of 223 pregnant women had fetuses diagnosed with CAs. The prevalence of structural CAs in pregnant women with low weight was of 20.18%, of 43.50% in pregnant women with adequate weight, of 22.87% in pregnant women with overweight, and of 13.45% in pregnant women with obesity. The prevalence of central nervous system (CNS) anomalies and of genitourinary system anomalies was high for the four groups of pregnant women. A positive association was observed between multiple anomalies in pregnant women with adequate weight (prevalence ratio [PR] = 1.65; p ≤ 0.004) and between anomalies of the lymphatic system in obese pregnant women (PR = 4.04, p ≤ 0.000).Conclusion The prevalence of CNS and genitourinary system anomalies was high in all of the BMI categories. Obese pregnancies were associated with lymphatic system anomalies. Therefore, screening and identification of the risk factors for CAs are important, regardless of the maternal BMI. Our findings reinforce the importance of discussing with pregnant women maternal nutrition and its effect on fetal development and on neonatal outcome.
Keywords: congenital anomalies; pregnancy; obesity; body weight; fetal ultrasonography